2006
DOI: 10.1038/nbt1255
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of artificial microRNAs in transgenic Arabidopsis thaliana confers virus resistance

Abstract: Plant microRNAs (miRNAs) regulate the abundance of target mRNAs by guiding their cleavage at the sequence complementary region. We have modified an Arabidopsis thaliana miR159 precursor to express artificial miRNAs (amiRNAs) targeting viral mRNA sequences encoding two gene silencing suppressors, P69 of turnip yellow mosaic virus (TYMV) and HC-Pro of turnip mosaic virus (TuMV). Production of these amiRNAs requires A. thaliana DICER-like protein 1. Transgenic A. thaliana plants expressing amiR-P69(159) and amiR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
362
1
8

Year Published

2007
2007
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 511 publications
(378 citation statements)
references
References 48 publications
7
362
1
8
Order By: Relevance
“…The advantages and effectiveness of amiRNA technology in plant systems have been verified from several studies using transgenic approaches (Alvarez et al, 2006;Niu et al, 2006;Schwab et al, 2006;Choi et al, 2007;Ossowski et al, 2008) since the first finding of amiRNA activity in Arabidopsis (Parizotto et al, 2004). Our study extends amiRNA versatility into Arabidopsis protoplasts.…”
Section: Functional Tools Of Reverse Genetic Studies Using Amirna In mentioning
confidence: 49%
“…The advantages and effectiveness of amiRNA technology in plant systems have been verified from several studies using transgenic approaches (Alvarez et al, 2006;Niu et al, 2006;Schwab et al, 2006;Choi et al, 2007;Ossowski et al, 2008) since the first finding of amiRNA activity in Arabidopsis (Parizotto et al, 2004). Our study extends amiRNA versatility into Arabidopsis protoplasts.…”
Section: Functional Tools Of Reverse Genetic Studies Using Amirna In mentioning
confidence: 49%
“…Recently, it has been demonstrated that the modification of plant endogenous miRNA precursors to interfere with viral mRNA sequences can confer virus resistance in Arabidopsis thaliana (Niu et al, 2006). These modified miRNA are termed artificial miRNA and this technique will open new perspectives for engineering viral resistant plants.…”
Section: Micro Rnamentioning
confidence: 99%
“…VIGS can be defined as the silencing of endogenous plant genes initi- repeats (Meister & Tuschl, 2004); (B) Dicer-like protein (DCL2, DCL3) processing of intermediates formed during RNA virus replication (Hannon, 2002); (C) Long dsRNA; (D) Dicer-like protein (DCL1) processing of miRNAs precursors ; (E) RNA-induced silencing complex (RISC) (Hammond et al, 2000;Nykänen et al, 2001); (F) Targeting and cleavage of sequence specific mRNA by RISC (Martinez & Tuschl, 2004); (G) mRNA destruction after RISC processing (Tolia & Joshua-Tor, 2006); (H) Possible systemic signal composed by siRNA + movement proteins; (I) Possible systemic signal composed by long dsRNA + movement proteins (Waterhouse et al, 2001); (J) Primer dependent RdRP amplification (Matzke et al, 2001;Ceruti, 2003;Baulcombe, 2004); (K) Primer-independent (aberrant RNA features) RdRP amplification (Baulcombe, 2004); (L) Primary siRNA (Pak & Fire, 2007); (M) Secondary siRNA processing by Dicer-like enzymes (Pak & Fire, 2007); (N) RNA-directed DNA methylation (RdDM) signal transmitted from the cytoplasm to the nucleus is most likely siRNA ; (O) RNAi effector complex termed RITS (RNA-induced Initiation of Transcriptional gene Silencing) required for heterochromatin assembly in fission yeast (Schizosaccharomyces pombe) (Verdel et al, 2004). RITS is composed by repeat-associated short interfering RNA (rasiRNA) (Meister & Tuschl, 2004); (P) Translational repression of mRNA by miRNP (Meister & Tuschl, 2004 In early approaches on VIGS studies, gene sequences were individually subcloned into viral genomes, and plants were physically inoculated using viral RNA produced by in-vitro transcriptional reactions (Kumagai et al, 1995).…”
Section: Virus Induced Gene Silencing (Vigs)mentioning
confidence: 99%
See 1 more Smart Citation
“…17,[45][46][47][48][49] The structural features of the endogenous miRNA precursor transcript on which an amiRNA plant expression vector is based are maintained while the miRNA/miRNA* duplex is replaced with amiRNA and amiRNA* sequences. Such a design ensures that the modified precursor transcripts are still recognized and processed by the protein machinery of the miRNA biogenesis pathway to produce a single specific 21-nt silencing signal.…”
Section: Artificial Mirna-directed Anti-mirna Technologymentioning
confidence: 99%